Assessment of pollutant emissions and energy efficiency of four commercialized charcoal stoves with modified Chinese cooking stove protocol - Zhang, Yixiang; Hao, Jiong; Zhou, Yuguang; Zhang, Zongxi; Chen, Li; Dong, Renjie (International Journal of Agricultural and Biological Engineering, 2018)
Charcoal stove is widely used in the developing countries especially in Africa and Central America. Even reported to have a high impact on human health, stoves promoted in the related areas still mainly focus on fuel saving and little knowledge was reported for the stove performance in the field. This research evaluated four commercialized charcoal stoves with clay baseline stove using a modified Chinese cooking stove protocol that considered the local cooking habit to make the testing results more useful for the local stove promotion. The results showed that the thermal efficiency of tested charcoal stoves ranged from 38.7% to 47.5%, and the cooking power was around 640-1200 W. The CO emission factors of the improved stove had a 60% reduction compared with baseline stove. Different indicators reporting the same aspect of the stove were evaluated, and it suggested choosing the indicators according to the project requirements.Keywords: charcoal stove, energy efficiency, pollutant emissions, carbon dioxide emissions, testing protocol, cookingDOI: 10.25165/j.ijabe.20181102.3637Citation: Zhang Y X, Hao J, Zhou Y G, Zhang Z X, Chen L, Dong R J. Assessment of pollutant emissions and energy efficiency of four commercialized charcoal stoves with modified Chinese cooking stove protocol. Int J Agric & Biol Eng, 2018; 11(2): 202–207.